EU VO LÁ ONTEM, PAPAI! ― EXPERIÊNCIA E CULTURAS INFANTIS: REFLEXÕES SOBRE INFÂNCIA E TEMPORALIDADE RECURSIVA - Sanhces, Eduardo Oliveira; Silva, Divino José Da (Centro de Estudos Educação e Sociedade - Cedes, 2016)
ABSTRACT: This theoretical study aims to carry out similarities between the philosophical thoughts of Walter Benjamin and sociological reflections of Manuel Jacinto Sarmento about childhood, recursive temporality, childish experiences and cultures. For this, we divided our exposition into four sessions that aim: to highlight the childhood as historical category in the modernity; to present Benjamin's look at the approach; to highlight the prospect through the Sarmento's optical; Finally, to approximate the concepts. We consider that the main approximation between from both is to rethink the meaning of social dynamics and the relations of social actors in the contemporary time, so not only the meanings of childhood today, but the own human condition at the present time.

RÉSUMÉ: Cette étude de nature théorique a comme objectif réalizer des approchement entre les pensances philosophiques de Walter Benjamin et les réflexions sociologiques de Manuel Jacinto Sarmento sur l'enfance, temporalité recursive, des esxpeciances et des cultures infantiles. Pour faire ceci nous avons divisé notre exposition en quatre sessions en visant: evidencier l'enfance comme catégorie historique dans na modernité; présenter le regarde benjaminian sur l'approche; mettre en evidence la perspective au moin de l'optique de Sarmento; et finalment, approcher les conceptions. En considerant que le principal approchement entre tous les deux c'est de repenser la significacion de las dinamiques sociaux et les relations des auteurs sociaux dans la comtemporanité, donc, pas seulement les sens de l'enfance dans la actualité, mais la propre condition humaine dans le temps présent.

RESUMO: Este estudo de natureza teórica teve por objetivo realizar aproximações entre os pensamentos filosóficos de Walter Benjamin e as reflexões sociológicas de Manuel Jacinto Sarmento sobre infância, temporalidade recursiva, experiência(s) e cultura(s) infantil(is). Para tanto, dividimos nossa exposição em quatro seções que visam: evidenciar a infância como categoria histórica na modernidade; apresentar o olhar benjaminiano sobre a abordagem; evidenciar a perspectiva por meio da ótica de Sarmento; por fim, aproximar as concepções. Consideramos que a principal aproximação entre ambos é a de repensar o significado das dinâmicas sociais e as relações dos atores sociais no contemporâneo, portanto, não apenas os sentidos da infância na atualidade, mas a própria condição humana no tempo presente.
I will be there yesterday, daddy! ― Experience for children and cultures: reflections about children and recursive temporality
Je vais la bas hier, mon père! ― De l'experience et de la culture de l'enfance: des réflexions sur l'enfance et la temporalité recursive
Keywords: Childhood; Recursive temporality; Experience; Children's culture; Sociology of Childhood; Infância; Temporalidade recursiva; Experiência; Cultura infantil; Sociologia da Infância